The Spectral Method for the Generalized Kuramoto-Sivashinsky Equation (Journal of Computational Mathematics, 2021)
A spectral method is proposed, the existence and uniqueness of the global and smooth solution are proved for the periodic initial value problem of the generalized K-S equation. The error estimates are established and the convergence is proved for the approximate solution of the spectral method.